FAKTOR- FAKTOR YANG BERHUBUNGAN DENGAN PEMILIHAN PENOLONG PERSALINAN DI WILAYAH KERJA PUSKESMAS SIPAHUTAR KECAMATAN SIPAHUTAR KABUPATEN TAPANULI UTARA TAHUN 2012 - Harto P Simanjuntak; Heru Santosa; Maya Fitria (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
One of the Indonesia's health development goals is to increase significantly the number of pregnant women check-ups and deliveries are handled by health personnels so the higher delivery by health coverage the lower the risk of maternal and child mortality. Scope of delivery by health Sipahutar health center working area by 70% and this figure has not yet reached the target indicator Sipahutar In 2011 the health center by 82% and target indicators Ministry of Health (MOH) Strategic Plan 2005-2009 and Indicators of Healthy Indonesia 2010 by 90%. This indicates that there is still births attended by traditional birth attendances( TBA). This study aimed to determine the factors associated with the selection of birth attendant working in the health center Sipahutar of North Tapanuli 2012. This research is an analytical survey of the cross-sectional design. Population is all women who gave birth in the health center work Sipahutar in 2011, amounted  353 people.The technique of sampling was proportional random sampling and 135 of them were selected to be sample. Data were collected by using questionnaries. Data analysis included univariate and bivariate by using chi-square test. The results of the study showed that 12.6% of respondents chose a traditional birth attendances. It was found there relationship between family income (p=0.005), knowledge of mothers (p=0.005), the cost of labor (p=0.001), maternal attitude (p=0.001) and family support (p=0.001) with birth attendant. From the results of the research are expected to the good cooperation between the health centers and village midwifes in improving births attended by health personnel to do counseling. Keywords: Delivery Assisted, Health Personnel.